The testing results of the new white lupine varieties and samples in the forest-steppe conditions of the Central Blackearth region - А. S. Blinnik; A. G. Demidova; L. А. Naumkina; О. Yu. Kurenskaya; М. I. Lukashevich (Зерновое хозяйство России, 2021)
The variety study of white lupine plants in the Belgorod region was carried out in field trials at the collection nursery of department of plant production, breeding and olericulture of the Belgorod State Agrarian University named after V.Ya. Gorin in 2018–2019. In the trial there were studied 4 varieties and 26 samples of white lupine of grain-fodder selection developed by the All-Russian Research Institute of Lupine, the variety ‘Michurinsky’ was taken as a standard one. Most of the samples in the trial significantly exceeded the standard variety in the value of seed productivity. In 2018 the highest yield of 4.86 t/ha was obtained from the sample ‘CH 40-15’, which was on 1.15 t/ha higher than that of the standard variety. A high yield from 4.19 to 4.82 t/ha was produced by the samples ‘СН 78-16’, ‘СН 20-13’, ‘СН 15-13’ and ‘СН 816-09’, which significantly exceeded the standard variety on 0.48–0.61 t/ha. Under the conditions of the year of 2019, a significant productivity increase (from 0.24 to 2.1 t/ha) in comparison with the standard variety was produced by 19 samples and two varieties ‘Pilgrim’ and ‘Timiryazevsky’. The largest productivity in the trial (5.26 and 5.24 t / ha) was produced by the samples ‘CH 54-08’ and ‘CH 12-13’. The yield increase of the samples ‘СН 77-17’, ‘СН 816-09’, ‘СН 1735-10’, ‘СН 17-14’ was 1.35–1.57 t/ha in comparison with the standard variety. The highest mean yield in the trial for 2 years (4.40–4.47 t/ha) was formed by the samples ‘СН 17-14’ and ‘СН 816-09’, their increase was 0.96–1.03 t/ha or 27.9–29.9% in comparison with the standard variety. The samples ‘СН 12-13’ and ‘СН 54-08’ showed the highest coefficient of adaptability in the trial at the level of 1.36–1.38. The most of the studied samples and the variety ‘Alyi Parus’ possessed the coefficient of adaptability >1, which characterizes them as highly adaptable to the arid conditions of the region. The most varieties and samples exceeded the standard value of the trait ‘seed weight per plant’ which is 4 g. The value of the trait ‘1000-seed weight’ in the trial varied from 234.8 g (the sample ‘CH 35-13’) to 302.6 g (the sample ‘CH 25-11’) in comparison with 264 g (the standard variety).